Between the police initiative and neighborhood participation: coercion, public security and State in Lima during the first years of the republican era (Palimpsesto, 2018)
The objective of this article is to analyze the state's coercive actions in relation to public security in Lima,during the early republic. It is argued that the deployment of police agents in the city, which had begun inthe late eighteenth century, generated new types of relationships between the State and society. Thepopulation went through a learning process through which they could identify and take advantage of thepossibilities generated by the permanent presence of police officers in the city, to safeguard their safety. Inthat sense, the Lima people came to them not only when their security was threatened or violated, but alsothat of their neighbors. In this way, not only police intervention was generated in the streets, but also in private spaces, which allowed to repress practices based systematically on physical violence, which couldlead to homicides.
Keywords: State; public security; coercion; police; serenos; Lima